Development Of Professional Competences of Students in Technical Field Based on Software Tools - Davronova Maxliyo Shamsiddin qizi (Global Scientific Publishing, 2024)
The article provides feedback on the development of professional competencies of students of technical universities. Recommendations for the use of software in the development of professional competencies are given. The capabilities of a number of software tools and the benefits of using them have been compared.
Keywords: professional competence; software; model; graphic editor